Sustainable Agriculture and Climate Change - Suren(dra) Nath Kulshreshtha (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Sustainability covers environmental, social and economic dimensions, and requires a multi-disciplinary approach in order to examine, explore and critically engage with issues and advances in its related areas. As we are aware, climate change is a certainty and it affects many economic sectors, including agriculture, particularly production of crop and livestock enterprises. Vast regional differences in these impacts are expected for various parts of the world, culminating in changes in trade patterns, and perhaps eventually even threatening the food security in certain parts of the world. Agricultural sustainability may be especially threatened by climate extremes, such as heat waves, droughts, and floods. However, not all changes induced by climate change would be negative; some may even be positive. Undoubtedly, there would be winners and losers within a nation, as well as among countries. Achieving sustainability would require changes in the way we manage agriculture. Equally important in this discourse is to find solutions to achieve sustainability in the wake of climate change, one of the major threats to sustainability. This book is devoted to various aspect of sustainable agriculture and climate change and their interplay.